Mechanical Characterisation of the Human Thoracic Descending Aorta: Experiments and Modelling - Garcia-Herrera, C; Cruchaga-Ssa., M (2012)
This work presents experiments and modelling aimed at characterising the passive mechanical behaviour of the human thoracic descending aorta. To this end, uniaxial tension and pressurisation tests on healthy samples corresponding to newborn, young and adult arteries are performed. Then, the tensile measurements are used to calibrate the material parameters of the Holzapfel constitutive model. This model is found to adequately adjust the material behaviour in a wide deformation range; in particular, it captures the progressive stiffness increase and the anisotropy due to the stretching of the collagen fibres. Finally, the assessment of these material parameters in the modelling of the pressurisation test is addressed. The implication of this study is the possibility to predict the mechanical response of the human thoracic descending aorta under generalised loading states like those that can occur in physiological conditions and/or in medical device applications. © 2012 Taylor & Francis.